The LOC Learning Model on Student Learning Achievement in Theme 7 of Sub-Themes 1 of The Science Content - Pidianti, Lilis; Taufik Saleh, Yopa; Nurfitriani, Meiliana (Universitas Pendidikan Ganesha, 2020)
This research talks about research that uses the Inside-Outside Circle (IOC), the learning model. This study aimed to determine the effect of the IOC learning model on student achievement on the theme 7 sub-themes 1 of science content in grade IV SDN Kersagalih. The type of research used in this study was quantitative by using Quasi-Experimental Design with the design of nonequivalent control group design. This research was conducted at Kersagalih Elementary School. The population was all students in grade IV Kersagalih Elementary School, totaling 30 students. The sample used was the entire population (total sampling), the sampling was a simple random sampling method. For the data collection techniques used tests that were pretest and posttest and the data were analyzed using the SPSS 25 application. From the results of the analyzed data, it was found that sig 0.003 <0.05, which means that H0 is rejected. The Inside-Outside Circle (IOC) Learning Model has a significant influence on the learning achievement of the fourth-grade students of SDN Kersagalih on the theme 7 sub-themes 1 of science content. Obtaining a t-count is 3.306 and the t-table is 2.04841. For t-count obtained in a positive region or 3.306> 2.04841 so that Ha is accepted. The average value of the experimental class is 82.33 and the control class is 70.33 (82.33> 70.33). So, the Inside-Outside Circle (IOC) learning model has a positive influence on the learning achievement of the fourth-grade students of Kersagalih Elementary School on the theme of 7 sub-themes 1 of science content.Â